Flouting Maxim as Social Criticism: Rhetorical Manifestations in Wilde’s The Importance of Being Earnest - Silva Rani; Almira Irwaniyanti Utami (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2026)
Language is not always used literally; speakers often communicate meanings that are not explicitly conveyed. This study investigates how flouting Grice's maxims functions as a pragmatic strategy generating social criticism in Oscar Wilde's The Importance of Being Earnest (1895). Previous research has treated Wilde's satire and irony as literary devices without examining maxim flouting as the underlying pragmatic mechanism, leaving a gap between pragmatics and literary studies. This study identifies flouting of the four Gricean maxims and examines how their rhetorical realization through irony, repetition, hyperbole, and simile contributes to criticism of Victorian norms on class, marriage, morality, and identity. Data were collected through close reading and analyzed in four stages: identifying flouting, examining rhetorical realization, decoding implicature, and categorizing social criticism. Findings show the quantity maxim is flouted most frequently, mainly through exaggeration, repetition, and irony, followed by relevance and manner, with no quality flouting found. Linking maxim flouting to rhetorical realization, this study offers a sociopragmatic model illuminating pragmatic deviation as a literary device, contributing to interdisciplinary work bridging pragmatics and literary criticism. The study concludes that Wilde's humor is a deliberate linguistic strategy exposing the falsity of Victorian aristocratic norms, rather than mere entertainment.